Microbiological and Consumer Acceptance Analysis of Cook- chill Food During Storage in Chiller - Frenky Miharja (Universitas Muhammadiyah Sidoarjo, 2020)
The aim of this research was to determine microbiology and consumer acceptance anal- ysis of cook-chill food during storage in chiller. This research was conducted in microbi- ology laboratory and served development room PT Aerofood ACS Surabaya from March until May 2019. The hedonic tes to determine consumer preference and descriptive method used to result microbiology test and consumer acceptance. The storage time in chillerconsisting sixth level i.e CF0 (Fresh), CF1 (one day in chiller), CF2 (two days in chiller), CF3 (three days in chiller), CF4 (four days in chiller), and CF5 (five days in chiller). The result of microbiology test incuding TPC, Enterobacter, and Escherichia coli during storage in chiller still conform the standart set by Aerofood ACS Surabaya. Consumer preferences indicated that there was significant differencesin the atribut of colour, aroma, texture, and taste based on storage time. For the storage up to three days in chiller, it is finely acceptable for consumers. Mean while in storage for four and five days, the acceptability was 30-50% of consumers stated to refused or not accept them due to the changes in texture, colour, and taste.